2009
DOI: 10.1089/hum.2008.142
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Liver Metastases After Intravenous Injection of Ad5/35 or Ad35 Vectors With and Without Factor X-Binding Protein Pretreatment

Abstract: Inefficient tumor transduction with targeted adenoviral vectors is largely due to unspecific virus sequestration by blood components, including coagulation factor X, and Kupffer cell scavenging. In this study, we show that preinjection of snake venom factor X-binding protein (X-bp) reduces hepatocyte transduction and increases the circulation time in blood of an intravenously injected, fiber-chimeric Ad5=35 vector. X-bp pretreatment resulted in improved Ad5=35 transduction of liver metastases and increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
(25 reference statements)
0
27
0
Order By: Relevance
“…Vector genomes were detected in the lung, liver, heart, kidney, and spleen at levels between 5 and 20 genome copies per cell ( Figure 5A). [26][27][28] Vector DNA levels in the gastrointestinal tract and ovaries were 2 orders of magnitude lower. We speculate that the vector PCR signals in the lung, liver, kidney, and spleen reflect transduced leukocytes either as part of residual blood or as tissue infiltrates.…”
Section: Safety Of IV Hd-ad5/35 11 Vector Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vector genomes were detected in the lung, liver, heart, kidney, and spleen at levels between 5 and 20 genome copies per cell ( Figure 5A). [26][27][28] Vector DNA levels in the gastrointestinal tract and ovaries were 2 orders of magnitude lower. We speculate that the vector PCR signals in the lung, liver, kidney, and spleen reflect transduced leukocytes either as part of residual blood or as tissue infiltrates.…”
Section: Safety Of IV Hd-ad5/35 11 Vector Injectionmentioning
confidence: 99%
“…Previously, we and others have shown that Ad5 entry into hepatocytes is mediated by Ad5 hexon protein interaction with coagulation FX 26,27 and that this pathway is inefficient if Ad5 vectors contain the short Ad35 fibers (such as in the Ad5/35 11 vectors used here), most likely due to a steric block of the FX-interacting domains within the Ad5 hexon. 28 (C) Levels of serum alanine transaminase and aspartate transaminase at day 3 after Ad injection. N 5 3.…”
Section: In Vivo Hspc Transduction In Humanized Micementioning
confidence: 99%
“…Approaches using Ad5/35 have had varied tumor targeting efficacy in vivo , with reports of low level transduction of breast and liver metastases [237,239,241]. However, delivery of Ad5/35 to liver metastases was improved using a snake venom FX-binding protein (X-bp), to inhibit the Ad5 association with coagulation FX [237].…”
Section: Retargeting Adenoviral Vectorsmentioning
confidence: 99%
“…While promising, it is impractical to incorporate the bridging molecule into an OAd system because effective incorporation of bridging molecules into progeny viruses is not easy [17]. In recognition of this fact, chimeric fiber approaches such as Ad5 / 3 (Ad5 vectors with the fiber knob domain of Ad3) are more frequently applied for OAds and chimeric OAds displays improved gene delivery and antitumor efficacy in many preclinical studies [18,28,3436]. Additionally, ColoAd1 (also known as enadenotucirev, EnAd), a complex and highly potent chimeric Ad3/Ad11p virus, was generated by a novel “directed evolution” approach for its ability to kill colorectal cancer cells[37].…”
Section: Adenoviral Transductional Targeting and Its Application Tmentioning
confidence: 99%